Mass Carbon Monoxide Poisoning in a Family: A Case Report from Nepalgunj - Mandal, Rajesh Kumar; Shakya, Nirmal; Risal, Sanket Kumar; Shah, Rajani KC (Nepal Journal of Health Sciences, 2022)
Carbon monoxide (CO) is a colorless, odorless gas produced as a by-product of the complete combustion of hydrocarbons. CO binds rapidly to Haemoglobin (Hb), leading to the formation of carboxyhemoglobin (COHb), so the oxygen-carrying capacity of the blood will be decreased and causing tissue hypoxia. We present the case of accidental carbon monoxide poisoning in a family where four members were reported dead and three unconscious in the morning after sleeping in a room with burning briquettes. Carbon monoxide poisoning can be fatal. Public awareness about such poisoning is essential for prevention.